The variability of the warm absorber in I Zwicky 1 as seen by XMM–Newton. Issue 2 (20th July 2018) - Silva, C V; Costantini, E; Giustini, M; Kriss, G A; Brandt, W N; Gallo, L C; Wilkins, D R
ABSTRACT: We present new XMM–Newton observations of the intriguing warm absorber in I Zwicky 1. This luminous and nearby narrow-line Seyfert 1 galaxy shows ionized absorption by two components of outflowing gas; a low and a high-ionization phase with log ξ ∼ 0 and log ξ ∼ 2, respectively. Detailed modelling of these data reveal a complex and variable multiphase warm absorber. However, we find the changes in the ionization state of the gas not to be straightforwardly correlated with the variability of the intrinsic continuum source, in apparent contrast with photoionization equilibrium. The observed variability hints instead at a close connection between the two gas components, possibly both directly connected to the accretion disc activity. We thus suggest a phenomenological model capable of explaining these observations, consisting of a clumpy outflow where the high and the low-ionization components are closely linked. Changes in ionization over the years are mainly driven by the different densities of the clumps crossing the observer's line-of-sight, in which the 'skin' layer facing the source accounts for the more ionized component.